2001
DOI: 10.1007/s004450100165
|View full text |Cite
|
Sign up to set email alerts
|

The formation of deep-sea Limu o Pele

Abstract: Deep-sea sheet hyaloclastite consists mostly of sand-sized blocky and splinter-shaped shards, but also contains subordinate mm-to cm-sized thin, curved, and wrinkled plates and sheets of sideromelane. This latter type of shard, termed Limu o Pele, has been observed forming subaerially on Kilauea by entrapment of water in flowing lava followed by expansion of steam to form large bubbles which burst into thin fragments. Deepmarine limu has been inferred, from comparative morphological studies and assessment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Subaqueous eruptions can lead to significant volcanic input (e.g., Fiske et al 2001;Maicher and White 2001;White et al 2003;Tani et al 2008). Fiske et al (2001, their p. 822) in particular note how the finestgrained fraction is missing from caldera deposits in the Izu-Bonin system.…”
Section: Reviewmentioning
confidence: 99%
“…Subaqueous eruptions can lead to significant volcanic input (e.g., Fiske et al 2001;Maicher and White 2001;White et al 2003;Tani et al 2008). Fiske et al (2001, their p. 822) in particular note how the finestgrained fraction is missing from caldera deposits in the Izu-Bonin system.…”
Section: Reviewmentioning
confidence: 99%
“…Lonsdale and Batiza (1980) reported the presence of extensive £ows of volcaniclastics on the summits of four seamounts 8001 200 m above the £anks of the EPR interpreted to have formed in deep-water phreatomagmatic eruptions (see also Batiza et al, 1984). Smith and Batiza (1989) documented extensive volcaniclastic deposits at depths from 1240^2500 m on six additional seamounts near the EPR and located several vent areas (see also Maicher et al, 2000;Maicher and White, 2001). These deposits occur at a depth where pressure would seem to preclude the normal exsolution of magmatic volatiles to such a degree that they disrupt (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Recognizing the morphologic similarity of deep sea and littoral limu, Maicher et al (2000) and Clague et al (2000) inferred that the same littoral hydrovolcanic process observed at Kīlauea's coastline also generated deep sea limu, and the process was quantified for limu in hyaloclastites at Seamount Six, Cocos Plate by Maicher and White (2001). Reduced limu bubble size in the deep sea (Clague et al 2000;Maicher and White 2001) as compared to in the littoral environment, was considered to be a consequence of the reduced expansion of seawater at high hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced limu bubble size in the deep sea (Clague et al 2000;Maicher and White 2001) as compared to in the littoral environment, was considered to be a consequence of the reduced expansion of seawater at high hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%